PENGARUH METODE PEMBELAJARAN KOOPERATIF DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA - WARMANSYAH, JHONI (JPUD - Jurnal Pendidikan Usia Dini, 2016)
The aim of this research is to understand the effect of cooperative learning methods and learning motivation toward mathematics learning outcomes. This research was conducted in SDN Gunung Batu 2 and SDN Purbasari 1 second semester of academic year 2015/2016, using experimental methods to design treatment by level 2 x 2 involving 44 samples. The technique of data analysis in this research is using Anova Two Paths to see the main effects and interactions, then using Tukey’s test to see modest effects. 1) The results of students’ learning mathematics is taught through learning methods TGT higher than students taught by NHT method. (F count = 14,50 > F table (Î± = 0.05) = 4,08). 2) There is an interaction effect between teaching methods and learning motivation toward mathematics learning outcomes (F count = 19,15 > F table (Î± = 0.05) = 4,08). 3) At the students who have high motivation to learn, learning outcomes mathematics given by the method TGT higher than students who are given the method NHT (F count = 20,82> F table (Î± = 0.05) = 3,11), and 4) In the students who have the motivation low learning, mathematics learning outcomes given the TGT method is lower than the students who are given the method NHT (F count = -1,05> F table (Î± = 0.05) = 3,11).